Ibaloy notions of homeland from memories of place: an oral history of Loakan, Baguio City - Bahni, Rosella Camte-; Villan, Vicente C. (Quezon City Asian Center, University of the Philippines Diliman, 2023)
This study analysed oral sources to situate memories of place that shaped Ibaloy notions of homeland which were evaluated to determine their implications to the Ibaloy homeland in Loakan. It is a qualitative research conducted among Ibaloys in Loakan, Baguio City using adivay as an indigenous method, oral history and ethnographic methods to gather data from memories of place and supplemented by documentary sources. Men1ories of place were analyzed using humanist geography, interpretive and indigenous approaches.

The study showed that Ibaloy notions of homeland conjure images of homeland in its physicality as ancestral land where Ibaloys originated, sourced their living, and spent their lifetime. Homeland is also perceived for its incorporeal value through the relational world view that binds indigenous people to the land, other people, and the Spirits, generating a sense of place and identity as Ibaloys. Both material and non-material values inherent in Ibaloy notions of homeland provided the compelling reasons to preserve the ancestral lands and maintain the homeland in Loakan because their existence and survival as a people depend on it.

This research created an oral history of Loakan homeland consisting of changing and continuing Ibaloy notions of homeland. It features oral history and place to produce a kasaysayang bayan of the Ibaloys in Loakan, Baguio City.

Key words: Ibaloys; memories of place; oral history; notions of homeland;
Ibaloy rituals
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman.
Keywords: Ibaloy rituals -- Philippines; Ibaloys--memories of place -- Philippines; Ibaloy rituals -- oral history -- Philippines; Ibaloy -- notions of homeland -- Philippines